2022
DOI: 10.1002/bdd.2311
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of tacrolimus in Chinese adult liver transplant patients

Abstract: Tacrolimus is widely used in organ transplantation to prevent rejection. However, the narrow therapeutic window and the large inter-and intra-individual variability in the pharmacokinetics (PK) of tacrolimus make it difficult for individualization of dosing. This study aimed at developing a population pharmacokinetic model for estimating the oral clearance of tacrolimus in Chinese liver transplant patients, and identifying factors that contribute to the PK variability of tacrolimus. Data of 151 liver transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…Both final models indicated that only the CYP3A5*3 genotype recipients significantly affected tacrolimus PK in liver transplant patients, consistent with published data ( Zhu et al, 2015 ; Teng et al, 2022 ). Liver transplant recipients with CYP3A5*1*3 or CYP3A5*1*1 had 16.8% higher CL pl /F and 36.5% lower K m values than those of CYP3A5*3*3 carriers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Both final models indicated that only the CYP3A5*3 genotype recipients significantly affected tacrolimus PK in liver transplant patients, consistent with published data ( Zhu et al, 2015 ; Teng et al, 2022 ). Liver transplant recipients with CYP3A5*1*3 or CYP3A5*1*1 had 16.8% higher CL pl /F and 36.5% lower K m values than those of CYP3A5*3*3 carriers.…”
Section: Discussionsupporting
confidence: 87%
“…POD, considered a major surrogate for many time-dependent variables ( Pou et al, 1998 ; Teng et al, 2022 ), was also identified as an alternative indicator of time-dependent factors in CL pl /F and K m in our study. This may be attributed to progressive CYP3A enzyme activity recovery in the intestine and liver, and steroid dose tapering after transplantation.…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, the presence of ethanol in TETSMs improves drug penetration through the minute holes created in the stratum corneum as a result of fluidization by enhancing the lipids fluidity and decreasing the density of the lipid bilayer [11]. Moreover, the addition of TAC to TETSMs gel formulations resulted in higher pharmacokinetic parameters of PRED, as TAC is previously reported to increase corticosteroids accumulation [45]. These findings support the fact that transdermal delivery bypasses first-pass metabolism for many active ingredients including corticosteroids.…”
Section: Comparative Pharmacokinetic Study Of Prednisolone Gel Formul...supporting
confidence: 70%
“…For example, Zhou et al (2021) reported initial dosage optimization of tacrolimus in pediatric patients with thalassemia major undergoing hematopoietic stem cell transplantation based on population pharmacokinetics, without azoles included as final covariates. Teng et al (2022) reported population pharmacokinetics of tacrolimus in Chinese adult liver transplant patients, without azoles included as final covariates. Chen et al reported that wuzhi capsule dosage affects tacrolimus elimination in adult kidney transplant recipients, as determined by a population pharmacokinetics analysis, without azoles included as final covariates (Lizhi .…”
Section: Discussionmentioning
confidence: 99%